Pedagogical Affordances of Autograph Technology in the Teaching of Functions: An Activity Theory Perspective - Matindike, Fanuel; Ramdhany, Virendra (Edumatica : Jurnal Pendidikan Matematika, 2025)
The proliferation of digital devices within education systems in most African countries during and after the Covid-19 pandemic has created greater opportunities for incorporating digital technologies into mathematics education. This paper reports on initial findings from a broader study that explored the implementation of dynamic mathematical applications in the teaching of functions in marginalized high schools in South Africa. The study utilized a qualitative case study research method, based on Grade 11 learners’ experiences during an instructional intervention programme, to investigate the pedagogical affordances offered by Autograph technology in teaching functions at an underprivileged high school. Adopting an inductive and descriptive approach, data were collected using ethnographic methods, which included observations, textual analysis, and transcripts from both task-based and open-ended interviews. The findings of the study were categorized and discussed under four themes, namely, motivation enhancement, representation competency, classroom interactivity, and constraints. The study established that the affordances of Autograph technology as a teaching tool can only be fully realized when its application is well aligned with the pedagogical context, subject matter, and the students involved. An Autograph-mediated pedagogical model is proposed to offer insights to mathematics educators on how the pedagogic use of dynamic mathematical applications can be optimized.